Cytogenetics characterization of Crenuchus spilurus (Günther, 1863): a remarkable low diploid value within family Crenuchidae (Characiformes) - Pazian, Marlon F. [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Springer Nature, 2018)
Conventional and molecular cytogenetic analyses were performed in specimens of the Neotropical Crenuchus spilurus freshwater fish species from a single location (Caeté River, Brazil). All specimens presented diploid values of 2n = 38 chromosomes (12 m + 4sm + 2st + 20a), the lowest reported for family Crenuchidae up to now. A single pair of nucleolar organizing regions (NORs) was detected in the subtelocentric chromosome pair no. 9 by silver-staining and fluorescence in situ hybridization (FISH) with 18S rDNA sequence-specific probe. Two pairs of 5S rRNA gene clusters were found either interstitial or terminally located in the long arms of the acrocentric chromosome pairs nos. 10 and 13. Heterochromatic regions were clearly observed in the short arms of the NOR-bearing chromosome pair and weakly-positive to the pericentromeric regions of most acrocentric chromosomes. Additionally, no sex chromosomes were identified in the surveyed specimens. Crenuchidae have signals of several mechanisms involved in karyotype diversification within this family: differential location of heterochromatin-rich regions, multiplication, and translocation of rDNA clusters, presence/absence of sex chromosomes, macrostructural changes in morphology and number of chromosomes. This variety of karyotype patterns reveals the importance of widening cytogenetic studies to more taxa for better know the chromosomal evolution occurred in this group.
Keywords: 18S and 5S rDNA; FISH; Freshwater fishes; Neotropical fishes